Effective ignition energy for capacitor short-circuit discharge in explosive environments - Dangshu, Wang; Likang, Yang; Liu, Shulin; Wang, Xinxia; Luwen, Song; Fengjuan, Wu (Frontiers in Physics, 2024)
Capacitors short-circuit discharge in explosive environments will ignite and detonate the surrounding explosive medium, cause dangerous accidents. Capacitors short-circuit discharge at low voltage is a kind of micro-nano discharge. Due to the discharge gap being only micro-nanometers, the discharge process, electrode consumption energy, ignition of explosive media ignition energy and other energy relationships are not clear. In order to study the relationship between capacitor storage energy and various kinds of dissipation energy when the capacitor is short-circuited discharged, this paper establishes the conical and spherical cylinder micro-bump model according to the morphology of cathode surface obtained by three-dimensional profile scanner and scanning electron microscope, respectively. This paper establishes the second-order non-chiral differential equation according to the principle of energy conservation and heat balance and deduces the relationship between the cathode surface temperature and the height of micro-bump, the conical angle, and the spherical radius, and calculates the energy consumed by the anode surface based on the theory of heat transfer. Based on the heat conduction theory, the energy consumed by the micro-bump on the cathode surface was calculated; the energy consumed on the anode surface was deduced from the heat conduction theory using the surface heat source as the loading heat source; the residual energy of the capacitor was calculated based on the discharge time and the voltage size before and after the discharge; and the effective energy of the gas was calculated based on the law of conservation of energy. Finally, the discharge channel energy and electrode consumption energy, the end of the discharge capacitor residual energy, are used to ignite the explosive gas effective ignition energy relationship.